KEKERASAN SEKSUAL TELEVISI TERHADAP WANITA - Sunarto, Sunarto (JURNAL ILMU SOSIAL, 2009)
The women’s violence issues is found in adult mass media. What kinds of women violence are found in a children’s televisin program in Indonesia. Gender structuration theory guided this research. It used critical discourse analysis. Doraemon, Crayon Shinchan and P-Man were the object’s research. The result showed personal violence on women that done psychologically, sexually, and functionally.